Kinetic Insight on Improved Chemi-Resistive Response of Hydrothermal Synthesized Pt Loaded TiO2 Nano-rods Toward Vapor Phase Isopropanol - Das, Priyanka; Mondal, Biswanath; Mukherjee, Kalisadhan (Frontiers in Materials, 2019)
Flower like microstructure composed of eccentrically grown vertically aligned titania nano-rods is prepared through spherical carbon template mediated hydrothermal route. Mechanistic pathways for the growth of said aesthetic architecture is proposed by studying their phase formation behavior and morphological features. Chemi-resistive type sensing properties of prepared titania flowers for the detection of isopropanol are studied by varying the sensor operating temperature (225-300oC) and vapor concentration (10-200 ppm). Distinguishable sensitivity of titania flowers is identified for the detection of even 10 ppm isopropanol. Catalytic amount of Pt nano-particles (synthesized through chemical method) are introduced over prepared flower like titania to improve further their sensitivity. The plausible isopropanol sensing mechanism over TiO2 flowers as well as influence of operating temperature and role of Pt nanoparticles as chemical sensitizer in enhancing the response is explained. The current response transients of both the TiO2 flowers and their Pt modified counterpart for detecting low concentration (10-50 ppm) of isopropanol are modeled in accordance to Langmuir-Hinshelwood reaction mechanism and the rate constants for the respective surface reactions are estimated. The higher rate constant for the interaction of isopropanol over titania flowers than Pt modified counterparts is explained using the concept of decaying depleted layer during sensing.